PENGARUH E-WOM, BRAND IMAGE, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MS GLOW DI KOTA BATAM - Hendra; Oktavia, Yunisa (SCIENTIA JOURNAL, 2025)
This study aims to analyze the influence of Electronic Word of Mouth (E-WOM), brand image, and product quality on purchasing decisions of MS Glow products in Batam. In the digital era, E-WOM is a key factor influencing consumer decision-making. Additionally, a strong brand image and guaranteed product quality play a significant role in driving purchasing decisions. A quantitative approach was used with a sample of 100 MS Glow consumers in Batam, selected using Slovin's formula, and data were collected through questionnaires. The analysis was conducted using multiple regression with SPSS 25. The results show that E-WOM (regression coefficient 0.582, t-value 12.544, p < 0.05), brand image (regression coefficient 0.626, t-value 12.214, p < 0.05), and product quality (regression coefficient 0.315, t-value 7.268, p < 0.05) have a significant positive effect on purchasing decisions. These findings suggest enhancing brand image, leveraging E-WOM, and maintaining product quality to boost purchasing decisions